WEBSITE SISTEM INFORMASI PEMETAAN CAGAR BUDAYA KOTA SERANG, PROVINSI BANTEN - Sari Lalita; Ery Dewayani; Bagus Mulyawan (Jurnal Ilmu Komputer dan Sistem Informasi, 2018)
Serang city is one of the many cities that are in the region of Indonesia with a variety of attractions, some of which can be regarded as a cultural heritage. But until now, the cultural heritage of Serang City is still not so well known by the wider community. Therefore, required a media that is able to introduce the cultural heritage of Serang City to be better known through the making of the website.A “Serang City Cultural Heritage Mapping Information System Website, Banten Province" was built to assist Balai Pelestarian Cagar Budaya Banten in introducing the cultural heritage of Serang City to the public as well as facilitate the prospective tourists in viewing information about the cultural heritage. The methods used in data collection are observation, interview, and questionnaire. This software development methodology using the SDLC method consists of 5 phases, namely Planning, Analysis, Design, Implementation, and Maintenance. This website is built using using PHP and MYSQL Programming Language as database server. This website has been tested able to display data and map of cultural heritage of Serang city completely.